2001
DOI: 10.1590/s0041-87812001000200005
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis in a newborn infant: a case report

Abstract: We report the case of a one-day-old newborn infant, female, birth weight 1900 g, gestational age 36 weeks presenting with necrotizing fasciitis caused by E. coli and Morganella morganii. The newborn was allowed to fall into the toilet bowl during a domestic delivery. The initial lesion was observed at 24 hours of life on the left leg at the site of the venipuncture for the administration of hypertonic glucose solution. Despite early treatment, a rapid progression occurred resulting in a fatal outcome. We call … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The most common causative agents are Staphylococcus aureus and aerobic streptococci (9, 10, 41, 43). However, several reports associating the enterobacterium Escherichia coli with SSTI have been published: E. coli was found to be the causative agent of neonatal omphalitis (7), cellulitis localized to lower or upper limbs (4, 6, 49), necrotizing fasciitis (1,25,28), surgical site infections (44), infections after burn injuries (37), and others. A study monitoring SSTIs during a 7-year period and encompassing three continents (Europe, Latin America, and North America) showed E. coli to be an important causative agent, since it was the third-most prevalent isolated species, preceded solely by S. aureus and Pseudomonas aeruginosa.…”
mentioning
confidence: 99%
“…The most common causative agents are Staphylococcus aureus and aerobic streptococci (9, 10, 41, 43). However, several reports associating the enterobacterium Escherichia coli with SSTI have been published: E. coli was found to be the causative agent of neonatal omphalitis (7), cellulitis localized to lower or upper limbs (4, 6, 49), necrotizing fasciitis (1,25,28), surgical site infections (44), infections after burn injuries (37), and others. A study monitoring SSTIs during a 7-year period and encompassing three continents (Europe, Latin America, and North America) showed E. coli to be an important causative agent, since it was the third-most prevalent isolated species, preceded solely by S. aureus and Pseudomonas aeruginosa.…”
mentioning
confidence: 99%
“…Streptococcal NF was reported in eight dogs from Canada (Miller et al 1996;Prescott et al 1997) but, to our knowledge, NF associated with E. coli has not been reported previously in dogs. Escherichia coli has been recognised as the sole causal organism in cases of NF in humans (Rehman et al 1998;Krebs et al 2001), but is more commonly reported as part of a mixed infection (Brook 1996). Extensive necrosis associated with E. coli is often attributed to microbial synergism (Rehman et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…NF is an infection of the skin, S/C fat, and superfi cial to deep fascia, and there is rapid dissemination and signs of systemic toxicity (Krebs et al 2001). A variety of bacteria and fungi have been implicated as causal organisms in cases of NF (Brook 1996;Stevens 2000;Goodell et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, extensive use of intrapartum antibiotics has been associated with major changes in the spectrum of organisms involved and their susceptibility to antibiotics. Morganella morganii is rarely encountered but may cause serious invasive infection in the pregnant woman or neonate 1–10 . This organism is characteristically resistant to many beta‐lactam antibiotics which may lead to delays in proper treatment.…”
mentioning
confidence: 99%